Cyanide detoxification efficiency of injection and soak of hydroxocobalamin, sodium nitrite and sodium thiosulfate for sea water ornamental fish - Hy, Le Ho Khanh; Ky, Pham Xuan; Ha, Dao Viet; Anh, Nguyen Phuong; Vy, Phan Bao; Thuyet, Doan Thi; Tram, Dang Tran Tu (Vietnam Journal of Marine Science and Technology, 2019)
The Oceanographic Museum offers interesting exhibits of several marine lives for tourist sightseeing and entertainment. These sea water ornamental fish are all caught in the wild. However, its health can be affected by cyanide poisoning during human fishing. Depending on the level of cyanide poisoning, fish can die after one and two weeks that caused economic damages for the museum. The present study is concerned with results of cyanide detoxification by using direct injection into cinnamon clownfish or soak of hydroxocobalamin, sodium nitrite and sodium thiosulfate with the aim of improving the health, survival and life time for fish, contributing to increasing economic efficiency for the Oceanographic Museum